Food Crises in Kabardino-Balkaria in 1920s. - A. H. Karmov (Научный диалог, 2021)
One of the little-studied episodes of the systemic crisis that gripped Russian territory at the beginning of the last century as a result of wars and revolutions, as well as social transformations in the countryside, is considered. The food situation in Kabardino-Balkaria in the 1920s is analyzed. The features of the research approach inherent in the works of regional historians of the Soviet period when examining the theme of famine in Kabardino-Balkaria in 1921—1922 and 1930 are revealed in the article. On the material of archival sources, the active role of local and central authorities in the fight against hunger in the region in 1921—1922 is shown. Particular attention is paid to the problem of the 1930 famine. The main reasons for the taboo of this topic and the lack of its scientific development are established. It is proved that the scale and consequences of the food crisis in Kabardino-Balkaria in 1930 was comparable to the similar phenomena of 1921—1922. The subject of the anti-collective farm movement, which began in the summer of 1928 and lasted until the completion of the collectivization of peasant farms in Kabardino-Balkaria, associated with the problem of the systemic crisis of the indicated period, is highlighted.